Pembelajaran Kitab Al-Hujjaj Al-Qath'iyyah dalam Perspektif Gender di Pondok Pesantren Mahasiswa - Mardliyah, Ikhda Khullatil; Hasanah, Dian Uswatun; Indriani, Nahrin (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2023)
Gender bias in learning the yellow book is rarely realized by the community, even by the students, both boys and girls. The novelty of this research is that there is no study with a gender perspective in learning the book Al-Hujjaj Al-Qath'iyyah. The primary purpose of this study is to describe a gender perspective in understanding the book Al-Hujjaj Al-Qath'iyyah at PPM Darussalam. This research is a qualitative descriptive study—data sources from events, informants, and documents. Data collection techniques are in the form of observation, in-depth interviews, and documentation studies. The data validation technique uses source triangulation—data analysis techniques using the Creswell model: organizing, transcribing, and analyzing data. The results of the study show that in teaching the book at Islamic boarding schools, it is necessary always to carry out an in-depth analysis of texts that can lead to different gender perspectives, as is the case with the discussion of women who are prohibited from pilgrimage in the book Al-Hujjaj Al-Qath'iyyah.